A prospective randomised controlled clinical trial comparing somatostatin and vasopressin in controlling acute variceal haemorrhage. Issue 6464 (26th January 1985) - Jenkins, S A; Baxter, J N; Corbett, W; Devitt, P; Ware, J; Shields, R
Abstract : Twenty two patients were entered into a randomised controlled clinical trial comparing the efficacy of somatostatin and vasopressin in controlling acute variceal haemorrhage. Somatostatin was significantly more successful in controlling acute variceal haemorrhage than vasopressin (p = 0.003). Furthermore, no complications were observed during treatment with somatostatin.